Relationships Between Career Adaptability and the Intention to Stay in Job Among Nurses Working in Critical Care Units - Samaneh Shirnasab; Marzieh Adel Mehraban; Mahboubeh Rasouli (Iran University of Medical Sciences, 2023)
Background & Aims One of the reasons for leaving the job among nurses can be the lack of career adaptability, which refers to ability to cope with changes in working conditions. This study aims to determine the relationship between career adaptability and the intention to stay in job among nurses working in critical care units of teaching hospitals in Tehran, Iran. Materials & Methods This is a descriptive-correlational study with a cross-sectional design that was conducted in 2022-2023 in critical care units of seven hospitals affiliated to Iran University of Medical Sciences. Participants were 220 nurses working in these units with at least 6 months of work experience, who selected by a stratified sampling method from different working shifts. Data collection was done online using a demographic form, the career adapt-abilities scale (with four dimensions of concern, control, curiosity, confidence), and an intention to stay in job questionnaire (with three dimensions of adaptation, sacrifice, communication). Descriptive statistics (Mean±SD, frequency, percentage) were used to describe the data, while Pearson's correlation test and regression analysis were used to assess the relationships between the study variables. Results The mean total score of career adaptability was 2.98±0.98 and the mean total score of intention to stay was 3.02±1. Among the dimensions of career adaptability, the highest average was related to concern (3.05±1.14) and the lowest score was related to curiosity (2.92±1.09). Among the dimensions of intention to stay, the highest score was related to sacrifice (3.06±1.09) and the lowest score was related to adaptability (2.98±1.1). A positive and significant relationship was found between career adaptability and the intention to stay in job (r=0.43, P<0.05).  Conclusion Career adaptability, especially its curiosity dimension, has a significant relationship the intention to stay in job among nurses working in critical care units. By addressing different dimensions of career adaptability in nurses, hospital managers can be able to safeguard nurse retention in hospitals and mitigate nurse turnover.